2023
DOI: 10.1002/pat.6082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution groups on the homopolymerization activity of methyl aryl diallyl ammonium chloride

Abstract: Dimethyl diallyl ammonium chloride (DMDAAC), recognized for its high positive charge density among the several diallyl quaternary ammonium cationic monomers, has been constrained in lipophilic applications by its structure. In this article, benzyl, p-methylbenzyl, and p-nitrobenzyl were introduced as structural modifications of DMDAAC to compensate for this. The effects of the introduced aryl structures on the molecular structure of the modified diallyl methyl aryl ammonium chloride and the polymerization acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Therefore, when the monomer molecules approach the active center in the reaction, they will encounter high hindrance potential barriers that prevent polymerization 29 . Xu's research indicated that the electron‐donating ability of the methyl group was inadequate to offset the negative effects of the steric hindrance 13 . Therefore, the polymerization activity of DMC was lower than that of DAC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when the monomer molecules approach the active center in the reaction, they will encounter high hindrance potential barriers that prevent polymerization 29 . Xu's research indicated that the electron‐donating ability of the methyl group was inadequate to offset the negative effects of the steric hindrance 13 . Therefore, the polymerization activity of DMC was lower than that of DAC.…”
Section: Resultsmentioning
confidence: 99%
“…29 Xu's research indicated that the electron-donating ability of the methyl group was inadequate to offset the negative effects of the steric hindrance. 13 Therefore, the polymerization activity of DMC was lower than that of DAC.…”
Section: Effect Of Initiator Concentration On Polymerization Ratementioning
confidence: 99%
See 1 more Smart Citation